THE MATEMATICAL MODEL OF CLARIFYING PROCESSES FOR INDUSTRIAL WASTEWATERS - Miodrag IOVANOV (Fiabilitate şi Durabilitate)
To minimize the SS amounts in the effluent from the settling tanks, SS predictive methods areneeded.By applying mathematical models, it is possible to predict the SS concentration from the settling tank;the predictions can be used in order to choose the best control action, that is whether changing the flow path isneeded or not whether changing the flow path is needed or not; whether mixing caused by the sludge removalfrom the tank should be stopped or limited.From the presented model, as well as from the graph of Gauss bell,we notice that the SS concentrations in the effluent from the settling tanks grow from m to m+3T(/x-m/<3T); i.e.the SS concentrations in the effluent from the settling tanks are Gaussian.